2015
DOI: 10.1097/brs.0000000000001093
|View full text |Cite
|
Sign up to set email alerts
|

Predicting Short-term Morbidity in Patients Undergoing Posterior Spinal Fusion for Neuromuscular Scoliosis

Abstract: 3.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
8
1
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 33 publications
(13 citation statements)
references
References 39 publications
2
8
1
2
Order By: Relevance
“…The rate of adverse events (pneumonia, post-operative complications) was 22.2%, which is similar to the rates of other studies 22 . Basques et al 22 found that higher levels of ASA classification were associated with longer hospital stays and higher rates of infection and adverse events. ASA classification was not evaluated in this study; however, 75% of the patients who presented complications had long hospital stays (20 days or more).…”
Section: Discussionsupporting
confidence: 89%
“…The rate of adverse events (pneumonia, post-operative complications) was 22.2%, which is similar to the rates of other studies 22 . Basques et al 22 found that higher levels of ASA classification were associated with longer hospital stays and higher rates of infection and adverse events. ASA classification was not evaluated in this study; however, 75% of the patients who presented complications had long hospital stays (20 days or more).…”
Section: Discussionsupporting
confidence: 89%
“…Compared to instrumented posterior fusion, instrumented posterior fusion with interbody took an average of 19 minutes of additional time (P , .001). Although operative time has been associated with an increased risk of adverse events in other studies, 34,35 the differences were not associated with different perioperative morbidity in the current study. Thus, the clinical significance of these relatively small differences is thought not to be great in this setting.…”
Section: Discussioncontrasting
confidence: 52%
“…NSQIP-P has been used to describe adverse events following common pediatric orthopedic procedures in order to identify procedures and patient characteristics associated with an increased risk of postoperative complications [26]. Other studies have considered outcomes after specific orthopedic procedures [27][28][29], most frequently involving the spine [30][31][32][33], as well as outcomes in orthopedic patients with specific risk factors such as obesity, congenital heart disease, or cerebral palsy [34][35][36]. To our knowledge, NSQIP-P has not been used to characterize outcomes after pediatric orthopedic oncology procedures.…”
Section: Introductionmentioning
confidence: 99%